SASTRA LISAN LOKAL SEBAGAI PEMBANGUN PENDIDIKAN MORAL - Silfia Hanani (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2011)
Literature that developed in communities around the world, conveyed in many ways one of which is delivered by oral, then called oral literature. When viewed from the history of human life, oral literature comes into this world is as old as human existence on earth, because literary writings known to man can write after read. Thus also, this oral literature is everywhere. As the oldest literature in human life, then there is little oral literature has a very significant role in shaping the character, culture and human behavior. In Minangkabau, oral literature is one of them known as bakaba. Kaba, the story brings many moral messages. Kaba is growing in Minangkabau society is inseparable from the tradition maota very popular in the lives of Minang. Kaba, usually also tells of the legends that have the formation of human morality, he is locality. Therefore, oral literature in the lives of local people Minangkabau he also became media indisputable moral education